Analysis of Bureaucratic Reform Through Delayering of Government Institutions in Indonesia - Aris Maulana; Fibria Indriati; Kemal Hidayah (Pusjar SKPP Lembaga Administrasi Negara, 2022)
The plan to simplify the bureaucratic structure by streamlining the echelon system is one of the strategies and breakthroughs of bureaucratic reform in Indonesia that was implemented in the first period (2010-2014) and the second period (2015-2019) of Bureaucratic Reform. However, on the other hand, a survey issued by the World Economic Forum shows that Indonesia is still experiencing some difficulties with implementing bureaucratic reforms and has not effectively used the delayering process in its implementation. The purpose of this study is to examine and analyze bureaucratic reforms through delayering of government institutions in Indonesia. This research uses a qualitative type of research with the method of literature review. Researchers have found 15 peer-reviewed journal articles within five years (2017-2021) that follow the research topic, which is then studied and analyzed to obtain comprehensive findings. The results showed that government agencies in Indonesia generally have undergone bureaucratic reforms but have not led to a specific delayering process. The Civil Service (ASN) Law passed in 2014 has also supported the spirit of administrative reform. This shows that delayering within government institutions in Indonesia can provide effective and efficient changes that occur within the governance management of government institutions in Indonesia.